Industrial Automated Systems: Instrumentation and Motion Control - Bartelt T. Terry (Delmar, Cengage Learning, 2011)
Industrial Automated Systems: Instrumentation and Motion Control will provide readers with state-of-the art coverage of the full spectrum of industrial maintenance and control, from servomechanisms to instrumentation. They will learn about components, circuits, instruments, control techniques, calibration, tuning and programming associated with industrial automated systems. Industrial Automated Systems: Instrumentation and Motion Control focuses on operation, rather than mathematical design concepts. It is formatted into sections so that it can be used to teach a variety of courses including mechatronics, electrical motors, sensors, variable speed drives, programmable logic controllers, servomechanisms, and various instrumentation and process classes. This book also offers readers a broader coverage of industrial maintenance and automation information than other books and provides them with a more extensive collection of supplements, including a lab manual and two hundred animated multimedia lessons on CD.